Interfacial structure design for triboelectric nanogenerators. Issue 3 (2nd June 2022) - Sun, Bianjing; Xu, Dan; Wang, Zengbin; Zhan, Yifei; Zhang, Kai
Abstract: Since the emergence of triboelectric nanogenerators (TENGs), new strategies, materials, and applications have been rapidly developed in the past few years to realize the efficient utilization of mechanical energy from the environment. In the pursuit of high performance, long‐term stability, and adaption in a comprehensive situation, it is necessary to fully understand the triboelectric effect and its related parameters by analyzing real‐time working status of TENG devices. This review focuses on the interface structures in TENG devices and the real‐time charge transfer process enhanced by the microstructures/nanostructures on dielectric layer surfaces, which are believed to be primely important in addition to the inherent properties of materials. Four modes of TENG operations, two main types interfaces as solid–solid interface and solid–liquid interface, as well as various materials used for device fabrication are discussed initially. Based on the real‐time working status, the interface structures of TENG devices are classified into three different groups as one‐dimensional, two‐dimensional, and three‐dimensional ones. In addition, the noncontact mode TENG devices are also described and are regarded as candidates for mechanical wear. Finally, existing challenges and the prospect of TENG devices based on the structural design of interfaces are summarized. Abstract : Based on the real‐time charge transfer process at the microstructures/nanostructures on dielectric layer surfaces, the interface structure design to fabricate complex surface structures including one‐dimensional, two‐dimensional, three‐dimensional, and noncontact interface in solid–solid as well as solid–liquid triboelectric nanogenerator devices plays a crucial role in pursuing high performance, long‐term stability, and adaption in a comprehensive situation.